PENERAPAN MODEL PEMBELAJARAN TALKING STICKBERBANTUAN MEDIA FLASH CARD UNTUK MENINGKATKANKEMAMPUAN BERBICARA PADA ANAK - Sugiantiningsih, Ida Ayu; Aditya Antara, Putu (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the improvement of speaking ability after the application of talking stick learning model assisted with flash card as media to improve the ability to speak to the group of children of B2 TK Kartika VII-3 Singaraja in 2018/2019 academic year. This research is a Class Action Research (CAR) which has been carried out with 2 research cycles. The subject of the study was the group of children of the TK Kartika VII-3 Singaraja B2, amounting to 18 children, consisting of 10 boys and 8 girls. The data collection methods used in this study were photos and videos observation and documentation methods. The data from research results were analyzed using descriptive statistical analysis methods and quantitative descriptive analysis methods. The results of data analysis showed that there was an enhancement of speaking ability after the implementation of cooperative learning model talking stick assisted by flash card, this can be seen from the enhancement in the average of percentage in the first cycle of 67.08% with the criteria being increased in the second cycle to 81.91% who are in high criteria. Therefore an increase in the average number of percentages from cycle I to cycle II is 14.83%. It can be concluded that the application of talking stick learning model assisted by flash card media can improve the ability to speak to the group of children of B2 TK Kartika VII-3 Singaraja in 2018/2019 academic year. Key words: talking stick learning model, flash card, speaking ability